Analysis of Flow Disturbance in a Stenosed Carotid Artery Bifurcation Using Two-Equation Transitional and Turbulence Models - Tan,FPP; Soloperto,G; Bashford,S; Wood,NB; Thom,S; Hughes,A; Xu,XY (Journal of Biomechanical Engineering, 2008)
In this study, newly developed two-equation turbulence models and transitional variants are employed for the prediction of blood flow patterns in a diseased carotid artery where the growth, progression, and structure of the plaque at rupture are closely linked to low and oscillating wall shear stresses. Moreover, the laminar-turbulent transition in the poststenotic zone can alter the separation zone length, wall shear stress, and pressure distribution over the plaque, with potential implications for stresses within the plaque. Following the validation with well established experimental measurements and numerical studies, a magnetic-resonance (MR) image-based model of the carotid bifurcation with 70% stenosis was reconstructed and simulated using realistic patient-specific conditions. Laminar flow, a correlation-based transitional version of Menter's hybrid k-/k- shear stress transport (SST) model and its “scale adaptive simulation” (SAS) variant were implemented in pulsatile simulations from which analyses of velocity profiles, wall shear stress, and turbulence intensity were conducted. In general, the transitional version of SST and its SAS variant are shown to give a better overall agreement than their standard counterparts with experimental data for pulsatile flow in an axisymmetric stenosed tube. For the patient-specific case reported, the wall shear stress analysis showed discernable differences between the laminar flow and SST transitional models but virtually no difference between the SST transitional model and its SAS variant.